The truce : lessons from an L.A. gang war - Umemoto, Karen (Cornell University Press, 2006)
This ethnography of a gang war in the Los Angeles neighborhood of Oakwood, just blocks from the famed Venice Beach boardwalk, provides a rare eyewitness account of the urban violence pervasive in the recent history of the United States. With seventeen people killed and more than fifty injured, the hostilities over ten months in 1993 and 1994 marked the peak of gang violence in the history of Los Angeles, a city once labeled the "gang capital of the nation." The conflict began as a quarrel among individuals, some of whom had gang affiliations. Over time, the feud engulfed families and soon grew into a sustained clash between African American and Latino gangs. Eventually, victims fell who were not members of opposing gangs, but who fit certain racial and gender profiles. The conflict began to take on the attributes of what one local newspaper sensationalized as a "race war."Karen Umemoto lived nearby during this conflict and undertook two years of ethnographic research during and immediately following the spate of killings. She now offers a nuanced analysis of the trajectory and eventual end of this acute crisis. Her interviews with gang members, neighborhood residents, business leaders, police officers, and gang-intervention workers reveal the complexity of contemporary American urban conflict. The Truce highlights the differences in interpretations among combatants, witnesses, and law enforcement agents and others whose actions often had unintended consequences. Drawing on her experience living in multicultural Los Angeles and on the latest scholarship in a wide variety of disciplines, Umemoto provides much-needed guidance for policymakers and concerned members of the public faced with violence in an ever-changing urban landscape.